Public and tribal community college institutional review boards: A national descriptive analysis - Ocean, Mia; Hirschi, Melissa (Community college journal of research and practice, 2016)
It is currently unknown how many Institutional Review Boards (IRBs) exist at community colleges. This study investigates the percentage of public and Tribal community colleges that have active IRBs. It also examines the potential relationships between states that allow community colleges to confer baccalaureate degrees, or that have articulation agreements, and community college IRBs. Data were drawn from the United States Department of Health and Human Services in conjunction with the American Association of Community Colleges and state department of education websites in order to create a national snapshot of active and deactivated IRBs at these institutions. It was most common for a state to have at least one IRB at public community colleges. Conversely, the majority of states with Tribal community colleges did not have IRBs. Further, while no association was found between states that allow community colleges to confer baccalaureate degrees, states with an articulation agreement were more likely to have an active IRB at their community colleges. Trends potentially unique to community college IRB implementation appeared evident, including one IRB to oversee a district or state of community colleges. Future research is needed to clarify the rationales behind these decisions. Creating an IRB is one way in which community colleges might claim a more active leadership role in being both subject and producer of scholarship in the literature.